2018
DOI: 10.1016/j.cub.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sun Navigation Requires Compass Neurons in Drosophila

Abstract: Despite their small brains, insects can navigate over long distances by orienting using visual landmarks [1], skylight polarization [2-9], and sun position [3, 4, 6, 10]. Although Drosophila are not generally renowned for their navigational abilities, mark-and-recapture experiments in Death Valley revealed that they can fly nearly 15 km in a single evening [11]. To accomplish such feats on available energy reserves [12], flies would have to maintain relatively straight headings, relying on celestial cues [13].… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
191
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(207 citation statements)
references
References 51 publications
16
191
0
Order By: Relevance
“…Neurons of the CX, notably the E-PG cells, have been shown to encode heading, an important idiothetic feature for path integration, while walking (Green et al, 2017;Seelig and Jayaraman, 2015;Turner-Evans et al, 2017) and in flight (Giraldo et al, 2018) and appear to contribute to ring attractor dynamics (Su 2017, Kakaria 2017). The position of the bump of activity in E-PGs that encodes heading can be updated with or without visual feedback, and we hypothesized they could be involved in LDM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons of the CX, notably the E-PG cells, have been shown to encode heading, an important idiothetic feature for path integration, while walking (Green et al, 2017;Seelig and Jayaraman, 2015;Turner-Evans et al, 2017) and in flight (Giraldo et al, 2018) and appear to contribute to ring attractor dynamics (Su 2017, Kakaria 2017). The position of the bump of activity in E-PGs that encodes heading can be updated with or without visual feedback, and we hypothesized they could be involved in LDM.…”
Section: Discussionmentioning
confidence: 99%
“…As a fly turns, a spatially localized "bump" of neural activity moves through this structure to encode the heading estimate. Both visual and non-visual inputs could update this heading representation, and when the animal was not moving, the bump remains in one place via apparent ring-attractor functionality (Giraldo et al, 2018;Green et al, 2017;Kakaria and de Bivort, 2017;Seelig and Jayaraman, 2015). In addition to representing features useful for orientated walking behaviors, representations in the CX show context-dependence based on an animal's state of activity (Martin et al, 2015;Weir et al, 2013), and neurons in the CX can causally modulate internal state (Donlea et al, 2018;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Catch-and-release experiments from a fixed point in the desert suggested that Drosophila (melanogaster and pseudoobscura) disperse into all directions equally and are able to keep straight headings over extended periods of time, while flying in environments which provide few visual landmarks 20,21 . For a better quantitative understanding of the mechanisms underlying such processes, skylight navigation experiments using virtual flight arenas therefore serve as an attractive platform for the study of the navigation skills of wild type insects, thereby providing the platform for testing transgenic specimens harboring well-defined circuit perturbations 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…First established using larger insects, these assays have become particular useful in the dissection of visual circuitry in Drosophila melanogaster, by taking advantage of its unique molecular genetic toolkit 1 . Since early adaptations to Drosophila 4,5 , virtual flight arenas have been used to quantify behavioral responses to a multitude of visual stimuli, ranging (for example) from moving edges, different colors, celestial bodies, learned shapes, to more complex visual scenes [6][7][8][9][10][11][12] . Visual responses of flying Drosophila melanogaster to linearly polarized light emanating from above (thereby simulating the celestial polarization pattern) using a flight simulator have also been demonstrated [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%